Optimization of surface plasmon resonance based biosensor for clinical diagnosis of the Epstein–Barr herpes virus disease - Khrystosenko, R.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
The influence of the sensitive element fabrication technology and noise performance of surface plasmon resonance (SPR) immunosensor on sensitivity and stability of operation inherent to the “Plasmon” series instrument has been investigated to improve reliability of diagnosis and treatment of the Epstein–Barr herpes virus disease. To minimize the effect of the temperature change induced noise, compensation (introduction of the reference channel) and stabilization (active thermal control) methods were applied, allowing to substantially enhance resolution of the used SPR sensor system.